The stars of Whistling Ridge - Baldwin, Cindy (Quill Tree Books, an imprint of HarperCollinsPublishers, 2021)
Ivy Mae Bloom is almost thirteen years old, her name is almost a complete sentence, and her family's RV is almost a home. Ivy desperately wants a place to put down roots, but it's her mama's job as a fallen star to tend the magic underpinning the world--a job that's kept Ivy's family living on the road since before Ivy was born. After Ivy steals Mama's entire supply of wish jars in the hopes of finding a place to call home, disaster strands her family in Whistling Ridge, North Carolina, with Mama's star sisters. Something is draining the magic from the town, and the star sisters can't pinpoint it. Ivy and her new friends find a clue in Whistling Ridge's history that might explain the mysterious threat. But how can she help the star sisters lift the curse if it means losing her best chance at a forever home?